2010
DOI: 10.1152/ajprenal.00722.2009
|View full text |Cite
|
Sign up to set email alerts
|

A metabolomics approach using juvenile cystic mice to identify urinary biomarkers and altered pathways in polycystic kidney disease

Abstract: RH. A metabolomics approach using juvenile cystic mice to identify urinary biomarkers and altered pathways in polycystic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 52 publications
4
37
1
Order By: Relevance
“…These data suggest that recessive PKD cells are reprogrammed to require exogenous glutamine for production of glutaminesourced 2-HG that may ultimately result in augmented RTE cell survival or proliferation. While there have been several studies examining the metabolic profile of ADPKD, including one from our laboratory (27,29), this study is the first to evaluate nontargeted metabolomics in recessive PKD. Our finding that glutamine addiction also occurs in a human ADPKD epithelial cell line suggests the possibility of a more general phenomenon such that targeting the glutamine pathway, for example, using GLS inhibitors, may be a novel therapeutic approach for renal cystic disease.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that recessive PKD cells are reprogrammed to require exogenous glutamine for production of glutaminesourced 2-HG that may ultimately result in augmented RTE cell survival or proliferation. While there have been several studies examining the metabolic profile of ADPKD, including one from our laboratory (27,29), this study is the first to evaluate nontargeted metabolomics in recessive PKD. Our finding that glutamine addiction also occurs in a human ADPKD epithelial cell line suggests the possibility of a more general phenomenon such that targeting the glutamine pathway, for example, using GLS inhibitors, may be a novel therapeutic approach for renal cystic disease.…”
Section: Discussionmentioning
confidence: 99%
“…This is unfortunate, because early diagnosis of ADPKD in at-risk patients might lead to interventions (some in the pipeline) that can slow its progression. Our laboratory has utilized the Jck cystic mouse model (which is no longer the ideal model for ADPKD) in a metabolic investigation of potential urinary biomarkers of cystic kidney disease; 14 we showed that the cystic mouse can be discriminated from its wild-type counterpart by urine analysis alone. At day 26 of life, before there is serological evidence of kidney dysfunction, affected mice are distinguishable by urine metabolomic analysis; this finding persists through 45 d until 64 d, at which time body weight differences confound the results.…”
Section: Applications Of Metabolomics To Kidney Diseasementioning
confidence: 99%
“…AN ELEGANT STUDY (7) is contained in an issue of the American Journal of Physiology-Renal Physiology that discovers potential urinary biomarkers that are relatively common metabolites from various metabolic pathways. While this author is not an expert in metabolism, the fact that purine metabolism was shown to be upregulated in the study evoked a "déjà vu all over again" response from this author to the findings.…”
mentioning
confidence: 99%
“…Indeed, the galactose metabolic pathway is also affected, yielding allantoic acid as another candidate biomarker (7). Other metabolites derived from purine and galactose metabolism were also upregulated along with a handful of other candidate biomarkers.…”
mentioning
confidence: 99%